(untitled) (International Journal of Engineering and Computer Science, 2017)
Using mobile technology for Sign language is really valuable, and can improve learners’ learning and communication capacity, using the mobile platform applications through the E-learning to enhance, support and facilitate teaching and learning for Deaf people. The proposed MMLSL is using portable mobile devices such as tablet PCs and smart phones through wireless transmission with special equipment that attached to the devices. The main goal of the proposed MMLSL is to integrate text, audio and video with interaction between participants. Mobile application software can educate a distance learner with up to date information with supporting materials, and other types of knowledge and communications.The proposed MMLSL convert the motion of the Sign language into to comprehensible Arabic text that the non-disabled person can understand. The previous technique communication channel links a deaf person to a non-deaf person. The reverse conversion is from voice to comprehensible Arabic text using existing programs such as (IBM via Voice) which support Arabic language. The proposed MMLSL use the Arabic Sign language that is finger spelling which indicate the Arabic letters. The proposed MMLSL has many advantages over normal learning as Helping the disabled to improve their knowledge and facilitate their needs, It motivates student towards learning, M-learning increases knowledge of the students, Because of its portability nature, mobiles are readily available for learners at all times, It allows students to learn anywhere, and anytime which in turn gives unique experience for learners , It is very helpful for learners those who are hesitate or reluctance to normal learning, It helps to focus on individual learners, and encourage them, and This type of teaching-learning method helps to develop self-confidence and self-esteem among hearing impaired children